Ebola virus disease: preparedness and infection control lessons learned from two biocontainment units. Issue 4 (August 2015) - Hewlett, Angela L.; Varkey, Jay B.; Smith, Philip W.; Ribner, Bruce S.
Abstract : Purpose of review: This review details infection control issues encountered in the management of patients with Ebola virus disease (EVD), with emphasis on how these issues were confronted in two biocontainment patient care units in the United States. Recent findings: There is a notable paucity of medical literature to guide infection control policies and procedures when caring for patients with EVD. Thus, the experience of the Serious Communicable Diseases Unit at Emory University Hospital and the Nebraska Biocontainment Unit at the University of Nebraska Medical Center serves as the basis for this review. Facility issues, staffing, transportation logistics, and appropriate use of personal protective equipment are detailed. Other topics addressed include the evaluation of patients under investigation and ethical issues concerning the safe utilization of advanced life support. Summary: This review intends to serve as a reference for facilities that are in the process of creating protocols for managing patients with EVD. Given the lack of literature to support many of the recommendations discussed, it is important to utilize the available referenced guidelines, along with the practical experiences of biocontainment units, to optimize the care provided to patients with EVD while strictly adhering to infection control principles.